Perubahan Budaya Organisasi Pendidikan Dalam Pembentukan Karakter Siswa di MTS Laboratorium UINSU Medan - Dwi Hartina; Isma Hayati; Nurroyian N; Hulga Ryan Shori; Accep Noor Akbar; Chandra Wijaya (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine changes in educational organizational culture in the formation of student character in the MTS Uinsu Lab, the success of school organizational culture in shaping student character as well as supporting and inhibiting factors for implementing school culture. A qualitative approach with a descriptive method is used to describe the data obtained through interviews with four informants, coupled with supporting data obtained in observation and documentation. which is used as supporting data in analyzing student character. The findings of this study indicate that there are several habituation activities as a change in organizational culture implemented in the school, including Changes in Organizational Culture, fond of reading which plays an important role in building student character, Teacher Success in Building Organizational Culture and Factors supporting the application of school organizational culture is the togetherness and kinship between school members and the participation of stakeholders in the application of school culture. Meanwhile, the inhibiting factors faced by teachers and school principals in applying school culture to the formation of student character are differences in student character and environmental and family factors that underlie student character.